Virtual Reality for Motor and Cognitive Rehabilitation From Clinic to Home: A Pilot Feasibility and Efficacy Study for Persons With Chronic Stroke - Jonsdottir, Johanna; Baglio, Francesca; Gindri, Patrizia; Isernia, Sara; Castiglioni, Carlotta; Gramigna, Cristina; Palumbo, Giovanna; Pagliari, Chiara; Di Tella, Sonia; Perini, Gloria; Bowman, Thomas; Salza, Marco; et al. (Frontiers in Neurology, 2021)
Aims: Continuity of care is an important issue in healthcare for persons after stroke. The present multi-center pilot study investigates the feasibility and efficiency of an innovative approach, the Human Empowerment Aging and Disability (HEAD), for digital-health motor and cognitive rehabilitation. The approach is explored within an in-clinic context (ClinicHEAD) and in continuity of care (HomeHEAD) for persons after chronic stroke. Methods: Thirty-four outpatients with chronic stroke (mean age 55 years, SD 13.7) participated. The HEAD VR protocol was administered in two consecutive phases: Phase I in clinic (ClinicHEAD) consisting of 4 weeks of 12 supervised HEAD rehabilitation sessions (45-min), including motor, cognitive and dual task for all participants; Phase II at home (HomeHEAD) consisted of 60 sessions of the same VR activities, 5 times/week for 3 months. All participants in the ClinicHEAD were allocated (ratio 1:2) to continue with tele-monitored home rehabilitation (HH, N = 11) or to follow usual care (UC, N = 23). Blind evaluation was carried out at baseline, after ClinicHEAD, after 3 months of HomeHEAD and at 3 months Follow-up. Primary outcomes were functional mobility [2-min Walking Test (2MWT)] and cognition [Montreal Cognitive Assessment (MoCA)]. Feasibility and acceptance were assessed with adherence to treatment and the System Usability Satisfaction. Within group analyses were done with dependent samples t-tests, and between groups HomeHEAD comparisons were carried out on change scores with independent samples t-test (p = 0.05, two tailed). Results: The HEAD protocol was feasible with good adherence both in the ClinicHEAD phase (92%) and HomeHEAD (89%) phase, along with good perceived system satisfaction. ClinicHEAD resulted in a significant increase in functional mobility (2MWT, p = 0.02) and cognition (MoCA, p = 0.003) and most secondary outcome variables. At 3 months follow up of HomeHEAD the HH_group showed a further significantly greater maintenance of functional mobility with respect to UC_group (p = 0.04). Conclusion: The HEAD VR protocol was feasible in clinical and at home tele-rehabilitation for persons in the chronic phase after stroke. In clinic the approach was effective in augmenting motor and cognitive abilities and at home it was effective in longterm maintenance of functional mobility, indicating its usefulness in continuity of care. Clinical Trial Registration:ClinicalTrials.gov, NCT03025126.